Preservation of minced raw meat using rosemary (Rosmarinus officinalis) and basil (Ocimum basilicum) essential oils - Abdela Befa Kinki; Tegene Atlaw; Tamene Haile; Beriso Meiso; Dessie Belay; Legese Hagos; Fikadu Hailemichael; Junaid Abid; Ahmed Elawady; Nida Firdous (Cogent Food & Agriculture)
The present study aimed to evaluate the effects of rosemary (REO) and basil (BEO) essential oils (EO) on minced raw meat samples. The meat samples were subsequently treated with various concentrations: 0.5%, 1.0%, and 1.5% (v/w) of rosemary (MR0.5, MR1.0, and MR1.5) and basil (MB0.5, MB1.0, and MB1.5) EO, respectively, as well as meat sample without EO treatment was used as a control. Afterward, the samples were stored at 4 °C and monitored for pH, Hunter CIEL*a*b* color and bacterial counts at 0, 7, 14, and 21 days. Results indicated that EO treatment offered a lower pH, particularly for BEO treatment as compared to the control. Samples treated with BEO presented the higher CIEL*a*b* (lightness, redness and yellowness) values followed by REO treatments as compared to the control during the entire storage periods. The addition of both EO to minced meat resulted in a significant (p < 0.05) reduction of tested bacterial counts, whereas increased throughout storage in the control sample. The growth of total bacterial counts was delayed by 3, 4.82, 3.48, and 4.81 log CFU/g of meat in MR0.5%, MR1.0%, MB0.5%, and MB1.0%, respectively. Coliform and Salmonella counts were observed in MR1.0%, MB0.5%, and MB1.0% and fully inhibited at the end of storage. In general, BEO and REO treatments effectively maintained pH, color measured as CIEL*a*b* and prevent bacterial growth in minced meat during storage at 4 °C, with pronounced efficacy of BEO.